2020
DOI: 10.1111/1759-3441.12298
|View full text |Cite
|
Sign up to set email alerts
|

“I'd be sleeping in the park, I reckon”: Lived Experience of Using Financial Counselling Services in South Australia*

Abstract: The need for non-profit financial services increases with economic hardship. Consumers' experience of accessing non-profit financial counselling services in South Australia was explored across five focus groups. Thirty-six participants discussed service efficiency and potential improvements. The qualitative analysis we completed revealed five themes. Regarding non-profit financial services: (i) Financial counsellors are life changers; (ii) Microfinance is "critical for survival"; and (iii) They're "hidden". Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…This supposition is supported by findings from a recent Australian study which reported large sections of the community face financial hardship and for some the hardship is "unseen" and people are unable or unwilling to ask for help. (Pollard et al 2020) If there is expansion of the onsite service in the future, it is vital that barriers to access are minimised and patients and hospital staff have greater awareness of the program.…”
Section: Discussion and Implications For Practicementioning
confidence: 99%
“…This supposition is supported by findings from a recent Australian study which reported large sections of the community face financial hardship and for some the hardship is "unseen" and people are unable or unwilling to ask for help. (Pollard et al 2020) If there is expansion of the onsite service in the future, it is vital that barriers to access are minimised and patients and hospital staff have greater awareness of the program.…”
Section: Discussion and Implications For Practicementioning
confidence: 99%
“…Financial counseling can also aid financially stressed individuals by improving their financial behavior and raising their confidence in financial skills (Bourova et al. , 2019; Pollard et al. , 2020).…”
Section: Progression Of Themes In the Last Five Yearsmentioning
confidence: 99%
“…Hayne (2019) too has advocated the importance of counseling services in achieving the financial well-being of deprived citizens. Financial counseling can also aid financially stressed individuals by improving their financial behavior and raising their confidence in financial skills (Bourova et al, 2019;Pollard et al, 2020). It also helps overcome individual behavioral biases (Hoechle et al, 2017).…”
Section: Financial Counselingmentioning
confidence: 99%
“…In terms of financial services and support, COVID‐19 has amplified the relevance of findings in the article by Pollard et al . (2020). The authors share compelling evidence of the vital role financial counsellors play in providing triage and critical care to those whose financial situations are overwhelming with little hope of well‐being.…”
Section: Contributions From This Special Issuementioning
confidence: 99%